Frequently reported adverse events of rebamipide compared to other drugs for peptic ulcer and gastroesophageal reflux disease - Eunkyeong Jang; Minju Park; Ji Eun Jeong; Ji Young Lee; Myeong Gyu Kim (Scientific Reports, 2022)
Abstract This study aimed to detect safety signals of rebamipide and search for adverse events (AEs) of rebamipide that are more common than those of other drugs for peptic ulcer disease (PUD) and gastroesophageal reflux disease (GERD) in the elderly population. A total of 101,735 AE reports for drugs used to treat PUD and GERD between 2009 and 2018 from the KIDS-KAERS database (KIDS-KD) were used. Disproportionality analysis was performed to calculate the proportional reporting ratio (PRR), reporting odds ratio (ROR), and information component (IC). Drug labels in Korea, Japan, and China were reviewed to identify signals that have been listed. AEs frequently reported in the elderly population were also analyzed. Seriousness and median time to AEs were evaluated for statistically significant AEs. A total of 14 signals were detected, and 4 signals (dry mouth, dermatitis, purpura/petechia, and fluid overload) were not listed on drug labels; however, they may be included as part of other listed AEs. In the elderly population, 11 AEs such as dyspepsia/indigestion/gastrointestinal distress, somnolence, dry mouth, and edema were common. These AEs were not serious and occurred within 2–9 days. This study identified possible AEs of rebamipide, a relatively safe drug.